Phosphate transport in brush-border membranes from control and rachitic pig kidney and small intestine. - Brandis, M (1987)
1. Na-Pi co-transport was analysed using renal cortical and small intestinal brush-border membrane vesicles which were isolated from control (normal, heterozygotes) and rachitic piglets (homozygotes). 2. A kinetic analysis of Na-dependent initial linear uptake of Pi was performed using vesicles obtained from control animals. The results suggest similar kinetic properties for the renal and small intestinal co-transport system. (i) A sigmoidal dependence on Na concentration of Pi uptake suggests the involvement of more than one Na ion in the co-transport. (ii) Increasing Na concentration leads to an increase in the apparent affinity of the transport system for Pi and has minimal effect on the apparent Vmax (maximum velocity of uptake). (iii) Increasing pH leads to an increase in Pi transport rate. 3. The kinetic characteristics of the Na-Pi co-transport system in vesicles obtained from rachitic animals were similar to those in controls. The apparent Vmax, but not the apparent Km (Michaelis constant) for Na and Pi, is reduced in intestinal and renal brush-border membranes isolated from rachitic animals as compared to control animals. Injection of vitamin D3, three days prior to killing of rachitic litter-mates, increased the Na-Pi uptake rate in the brush-border membrane vesicles isolated from these piglets. 4. It is concluded that intestinal and renal brush-border membranes from piglets contain a similar Na-Pi co-transport system and that in vitamin-D-dependent rickets the number of operating transport units is reduced in both membranes.